Management and outcomes of acute myocardial infarction in patients with preexisting heart failure: an analysis of 2 million patients from the national inpatient sample. (4th March 2022) - Abramov, Dmitry; Kobo, Ofer; Mohamed, Mohamed; Roguin, Ariel; Osman, Mohammed; Patel, Brijesh; Parwani, Purvi; Alraies, Chadi; Sauer, Andrew J.; Van Spall, Harriette G.C.; Mamas, Mamas A.
ABSTRACT: Background: Inpatient management and outcomes of patients presenting with acute myocardial infarction (AMI) with a history of heart failure (HF) have not been well characterized. Methods: Hospitalizations for AMI from the Nationwide Inpatient Sample (2015–2018) were categorized according to a preexisting diagnosis of HF with preserved ejection fraction (HFpEF), reduced ejection fraction (HFrEF), or absence of HF. Utilization of invasive management and in-hospital outcomes were analyzed. Results: Among 2, 434, 639 hospitalizations with an AMI, 19.8% had a history of HFrEF and 11.9% had a history of HFpEF. Coronary angiography and PCI respectively were performed significantly less among patients with HF (36.6% and 17.4% in HFpEF, 51.1% and 24.6% in HFrEF, and 64.4% and 42.3% among patients without HF, all p < 0.0001). Mortality was more common among patients with HFrEF (10.3%) and HFpEF (8.3%) when compared to patients without a history of HF (6.4%), p < 0.0001.   Conclusion: HF is a common preexisting comorbidity among patients presenting with AMI and is associated with lower utilization of invasive procedures and higher complications including mortality, particularly among those with HFrEF.